QTL mapping in a maize F2 population using Genotyping-by-Sequencing and a modified fine-mapping strategy - Wang, Jian; Zhang, Xuan; Lin, Zhongwei (Plant science, 2018)
Maize possesses a tremendous genetic diversity, most of which is deposited in a large number of landraces. However, the genetic basis of local diversity from maize landrace remains largely unknown. Traditional fine mapping of the causal gene for complex trait, based on the transition from the quantitative trait locus (QTL) to a single qualitative gene through backcrossing or the construction of heterogeneous inbred family (HIF), has achieved great success in model crop rice. However, this fine-mapping strategy did not work well in maize. In this study, an F2 population derived from a maize landrace and an elite inbred line was firstly genotyped by genotyping by sequencing (GBS). QTL analysis further revealed 29 QTLs of 12 traits, most of which individually accounted for more than 10% of phenotypic variations. Next traditional fine-mapping method successfully narrowed down a major QTL of kernel color qCOK1, but failed in the fine mapping of another major QTL of ear height EH4 because the EH4 remained quantitative feature in the HIF. Based on the quantitative feature of the EH4 in the HIF, we then performed the correlation tests between genotypes and phenotypes in the descendant populations derived from the recombination plants to enable the process of fine mapping. Our modified fine-mapping strategy successfully narrowed down the EH4 into a 3.23-Mb region on chromosome 8. The modified fine-mapping method can be applied to fast clone the QTLs originated from maize landraces.
Keywords: Zea mays; Genotyping by sequencing; Sequence Analysis, DNA; QTL mapping; Genotyping Techniques; kukuřice setá; Phenotype; Genotype; genotypizační techniky; Major QTL; sekvenční analýza DNA; Quantitative Trait Loci; Fine mapping; fenotyp; Chromosome Mapping; genotyp; mapování chromozomů; lokus kvantitativního znaku; Maize landrace